2019
DOI: 10.1007/s12520-019-00837-0
|View full text |Cite
|
Sign up to set email alerts
|

Behind the steps of ancient sheep mobility in Iberia: new insights from a geometric morphometric approach

Abstract: In Western Europe, the transition from the middle Iron Age to the early Roman period implied changes in livestock practices, with the emergence of a specialized and selective animal husbandry. These changes have been related in Italy and south of France with changes in livestock management involving their mobility between ecologically complementary areas. The study of this question in the Iberian Peninsula has only been partially investigated through palaeoenvironmental analyses, and the information about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 37 publications
0
9
0
3
Order By: Relevance
“…Case studies from the mountain and lowland sites of Iron Age–Roman period Spain demonstrated a gradual change towards specialized economies, which involved increased focus on exploitation of sheep/goats and production of wool (Colominas, 2011; Colominas, 2013; Colominas, 2017). Geometric morphometric analysis conducted on the sheep astragali from the Spanish sites indicated a change of sheep breed from the Iron Age to the Roman period, which was likely associated with the establishment of specialized economies (Colominas et al, 2019; Colominas, Palet, & Garcia‐Molsosa, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Case studies from the mountain and lowland sites of Iron Age–Roman period Spain demonstrated a gradual change towards specialized economies, which involved increased focus on exploitation of sheep/goats and production of wool (Colominas, 2011; Colominas, 2013; Colominas, 2017). Geometric morphometric analysis conducted on the sheep astragali from the Spanish sites indicated a change of sheep breed from the Iron Age to the Roman period, which was likely associated with the establishment of specialized economies (Colominas et al, 2019; Colominas, Palet, & Garcia‐Molsosa, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…1 (2020) ISSN: 0079-8215 EISSN: 2339-9171 (p. 7-27) al., 2006;Davis et al, 2012;Colominas et al, 2015) y, en GMM, también los astrágalos (p. ej., Colominas et al, 2019;Pöllath et al, 2019).…”
Section: Muestreo Conservación Y Límites De Unas Disciplinas En Desarrollounclassified
“…Esta especie probablemente llegó a través del comercio marítimo, tal vez desde el área de Cartago, y su abundancia en el registro (un 83% en un conjunto de 242 mandíbulas) demuestra la ocupación eficaz del nicho ecológico por parte de la forma comensal ya en el siglo iv aC (Valenzuela-Lamas et al, 2011). Mientras en Francia hay varios estudios sobre bovinos y suinos para explorar los cambios en el tamaño y la identificación de poblaciones y morfotipos durante la prehistoria reciente y época clásica (Nuviala et al, 2014;Duval et al, 2015Duval et al, , 2018, el primer trabajo en la península ibérica ha aparecido hace solo unos pocos meses (Colominas et al, 2019). El estudio revela que las ovejas analizadas del Pirineo y el área del Empordà son morfológicamente diferentes en la Edad del Hierro, mientras que en época romana es probable que haya una mayor circulación de animales entre las dos zonas.…”
Section: Morfometría Geométricaunclassified
See 1 more Smart Citation
“…However, only few studies have employed geometric morphometrics on caprine bones. For sheep and goat, this includes studies of the talus with the aim of distinguishing archaeological sheep and goat (Haruda, 2017), differentiate ancient wild sheep from modern and archaeological domestic sheep (Pöllath et al, 2018(Pöllath et al, , 2019, and investigate the variation between archaeological sheep morphotypes (Colominas et al, 2019;Haruda et al, 2019;Vuillien, 2020).…”
Section: Introductionmentioning
confidence: 99%